Accelerating progress towards gender equality and biodiversity objectives - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
Gender dimensions are central to understanding and effectively responding to the world’s most pressing biodiversity management and conservation challenges. This infographic brings attention to the ways that addressing pervasive gender inequalities and taking a gender-responsive approach can enhance the conservation and sustainable use of biodiversity and the fair and equitable sharing of benefits derived from the utilization of genetic resources.